The Systems-Based Mentoring Model within the process of technology integration - Gökoğlu, Seyfullah; Öztürk, Mücahit; Çakiroğlu, Ünal (Participatory Educational Research (Per), 2015)
In recent, numerous attempts, approaches, and models related to the technology integration process are introduced. In those models, generally the teachers are located at the center of the process. Thus, it is important to choose a technology integration model in order to prepare the teachers for the technology integration, enable them to use the current and new technologies, intensify their belief related to new teaching technologies, and eliminate the barriers they may encounter during this process. In this context, the Systems-Based Mentoring Model comes into prominence at the point of resolving the problems that the teachers encounter in the learning environments. In the model, technology leadership is adopted as the main approach to the professional development of the teachers. It is stated that technology leader could play a supportive role against various barriers which the teachers are willing to integrate the technology (time, attitude, access, culture, professional development, etc.) and various strategies are presented in order to create a vision for technology integration, modelling the use of technology and training leader teachers. In the model, the teachers pass throughout various stages and they are encouraged to utilize the technology. The final objective of the model is to perform the technology integration through evaluating the current resources in schools and establish an integrated culture within the system which is supported by the teachers and the school administrators. It is important that supporting teachers by the experts for them to realize the technology integration transformation. Accordingly, the Systems-Based Mentoring Model has an importance of emphasizing the importance of technology leaders in encouraging and supporting the teachers during the integration process to reveal the roles of those leaders that should take over
Keywords: technology integration models; systems-based mentoring model; technology leadership; teachers; Eğitim Üzerine Çalışmalar; Studies on Education; 4. Education